DIFFERENCES IN ACHIEVEMENT BETWEEN ADOLESCENTS WHO REMAIN IN A K‐8 SCHOOL AND THOSE WHO TRANSITION TO A JUNIOR HIGH SCHOOL - Whitley, Jessica; Lupart, Judy; Beran, Tanya (Canadian Journal of Education/Revue canadienne de l'éducation, 2007)
There has been abundant research examining how early life experiences affect achievement. In this article, we investigate the transition from elementary to junior high school at a developmental stage where numerous changes have an impact on students. Using nationally representative survey data, we found no differences in academic achievement between students who transitioned to grade seven from an elementary school in comparison to those who remained in the same school. We did find a significant decline in mathematics achievement between grade five and grade seven for children, regardless of their transition status. We present a developmental, rather than environmental, explanation. Key words: school adjustment, adolescent development, mathematics achievement Il existe de nombreuses recherches sur l’effet des expériences vécues durant l’enfance sur la réussite scolaire. Dans cet article, les auteures étudient la transition d’une école primaire à une école secondaire du premier cycle à un stade du développement où de nombreux changements ont un impact sur les élèves. Se servant de données d’enquête représentatives à l’échelle nationale, les auteures n’ont trouvé aucune différence dans le rendement scolaire entre les élèves qui sont passés en 7e année dans une autre école par rapport à ceux qui sont restés à la même école. Elles ont noté toutefois une diminution importante des notes dans les examens de mathématiques entre les enfants de 5e année et ceux de 7e année, transition ou non. Il s’agirait, selon les auteures, d’une question de développement plutôt que de milieu. Mots clés : adaptation scolaire, développement à l’adolescence, rendement scolaire en mathématiques